Antibacterial potential of crude culture extract of Lactic acid bacteria on mastitis pathogens - Geetha, R (Indian Journal of Dairy Science, 2015)
A study was conducted to detect the inhibitory activity of crude culture extract (CCE) containing antimicrobial compounds from Lactic acid bacteria (LAB) isolated from naturally fermented food materials, against clinical isolates of mastitis pathogens viz., Escherichia coli (E.coli), Staphylococcus aureus (S.aureus) and Streptococcus agalactiae (S.agalactiae). Out of 52 isolates screened, CCE from 12 LAB isolates (Ce-2, Ce-4, Ce-5, De-4, Te-6, CRe-1, CUe-2, CUe-3 and Me-2) showed positive zone of inhibition against selected test pathogens. The sensitivities of test pathogens differed significantly to CCE of different isolates of LAB. S.agalactiae and E.coli were comparatively more sensitive to the CCE of the 12 LAB isolates. But S.aureus was comparatively resistant and showed response only to Te-5, CRe-2 and CRe-3 (CCE of LAB isolated from tomato and carrot). A significantly high antimicrobial efficiency against test pathogens was shown by treatments Te-5, CRe-2 and CRe-3, where a zone of inhibition ranging from 7.66±0.33 to 9.33±0.66 mm diameter was observed. The inhibitory action of crude culture extract was not affected significantly during storage at 4oC for four months and a remarkable antimicrobial spectrum ranging from 6.66±0.33 to 8.33±0.33 mm diameter still maintained. The LAB isolates, T-5 (Lactobacillus), CR-2 (Streptococcus) and CR-3 (Enterococcus) were considered as the most effective inhibitory compound producers.